Cloud-based IoT solution to control and monitor a psychrometric laboratory in a Peruvian University (LACCEI, 2024)
During the years of the COVID-19 pandemic, university education had to adapt to a virtual context and the laboratories, which made use of specialized equipment, had to stop and move to a simulated context, providing an experience for the student close to reality, but not complete. As the years progressed and the restrictions began to diminish, various alternatives were proposed to facilitate remote access by students to the laboratories through cameras, IoT solutions for the remote control and monitoring of specialized equipment through web environments. The Pontificia Universidad Católica del Perú has a psychrometric bank for laboratories of undergraduate courses, which could only be used in person. In this article, an IoT solution deployed in the cloud is proposed, with AWS services, to remotely control and monitor all the data generated by the psychometric bank. These data are obtained through sensors or cameras to be sent to the IoT platform in the cloud through MQTT, which will then allow users to see the result in real time using HTTPs and WebSocket. The deployed solution also allows managing user access by role, by date, assigning sensors to users in real time, saving a history of everything sensed, and exporting all the data generated during the laboratory session. The solution has also been used throughout a period of 12 months in which students have been able to interact with the platform, both in person and remotely.